Flexural Behaviour of CFS Gapped Built-up Channel Beam with Web and Flange Stiffeners - P. Sangeetha,; S. Dhanus,; Ba J Hrushikesh,; T Sreeharini, (International Journal of Integrated Engineering, 2025)
This study investigates the structural performance of cold-formed steel (CFS) gapped built-up beams with flange and web stiffeners, focusing on load-carrying capacity and deflection characteristics. Experimental tests and finite element (FE) analysis were conducted to evaluate the influence of varying stiffener configurations and gap sizes on beam behavior under four point bending. Results indicate that beams with flange stiffeners exhibit higher load-carrying capacity and greater resistance to deflection compared to those with web stiffeners, due to improved stability against bending stresses. Increasing gap between the back to back channel from 25 to 100 mm was found to affect load distribution and deflection, with moderate gaps (50 mm) yielding optimal performance. The FE model showed good correlation with experimental results, though deflection under ultimate loads was slightly underpredicted, highlighting the impact of real-world imperfections. These findings provide valuable insights for designing optimized CFS gapped beams with enhanced structural efficiency by providing flange and web stiffeners for practical applications.